Managing the cost overrun risks of hydroelectric dams: An application of reference class forecasting techniques - Awojobi, Omotola; Jenkins, Glenn P. (Pergamon-Elsevier Science Ltd, 2016)
Hydropower investments have been subject to intense criticism over environmental issues and the common experience with cost uncertainty. In this study we address the issue of uncertainty in cost projections by applying reference class forecasting (RCF) in order to improve the reliability of costs used for making decisions under uncertainty. This technique makes it possible to closely link contingency estimates to the likely incidence of uncertainty of construction costs for hydroelectric dams. A case study, the Bujagali dam in Uganda, is used to demonstrate how investment appraisal can be enhanced to better account for the risk of cost overruns. While this project has suffered from cost overruns, the net benefits of the dam are still expected to be substantial. We conclude that if historical information from the major financiers of dams is accessible, learning from the past can help to reduce the cost of uncertainty in power planning worldwide. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Hydropower; Cost uncertainty; Investment appraisal; Reference class forecasting; Bujagali